ONT long-read WGS for variant discovery and orthogonal confirmation of short read WGS derived genetic variants in clinical genetic testing - Kaplun, Ludmila; Krautz-Peterson, Greice; Neerman, Nir; Stanley, Christine; Hussey, Shane; Folwick, Margo; McGarry, Ava; Weiss, Shirel; Kaplun, Alexander (Frontiers in Genetics, 2023)
Technological advances in Next Generation Sequencing dramatically increased clinical efficiency of genetic testing, allowing detection of a broad variety of variants, from single nucleotide events to large structural aberrations. Whole Genome Sequencing (WGS) has allowed exploration of areas of the genome that might not have been targeted by other approaches, such as intergenic regions. A single technique detecting all genetic variants at once is intended to expedite the diagnostic process while making it more comprehensive and efficient. Nevertheless, there are still several shortcomings that cannot be effectively addressed by short read sequencing, such as determination of the precise size of short tandem repeat (STR) expansions, phasing of potentially compound recessive variants, resolution of some structural variants and exact determination of their boundaries, etc. Therefore, in some cases variants can only be tentatively detected by short reads sequencing and require orthogonal confirmation, particularly for clinical reporting purposes. Moreover, certain regulatory authorities, for example New-York state CLIA, require orthogonal confirmation of every reportable variant. Such orthogonal confirmations often involve numerous different techniques, not necessarily available in the same laboratory and not always performed in an expedited manner, thus negating the advantages of “one-technique-for-all” approach, and making the process lengthy, prone to logistical and analytical faults, and financially inefficient. Fortunately, those weak spots of the short read sequencing can be negated by long read technology that has comparable or better detection of some types of variants while lacking the mentioned above limitations of short read sequencing. At Variantyx we have developed an integrated clinical genetic testing approach, augmenting short read WGS-based variant detection with Oxford Nanopore Technologies (ONT) long read sequencing, providing simultaneous orthogonal confirmation of all types of variants with the additional benefit of improved identification of exact size and position of the detected aberrations. The validation study of this augmented test has demonstrated that ONT sequencing can efficiently verify multiple types of reportable variants, thus ensuring highly reliable detection and a quick turnaround time for WGS-based clinical genetic testing.